Hubungan antara Kepuasan Hidup dan Pengobatan Emfisema - Milna Sari; M. Agung Rahmadi; Helsa Nasution; Luthfiah Mawar; Ika Sandra Dewi; Romaito Nasution (Pusat Riset dan Inovasi Nasional, 2024)
This study investigates the relationship between life satisfaction and adherence to emphysema treatment through a comprehensive meta-analysis. Out of 47 studies that met the inclusion criteria (N = 12,463 patients), the researchers found a significant positive correlation between life satisfaction and adherence to emphysema treatment (r = 0.58, p < 0.001). Additionally, hierarchical regression analysis revealed that life satisfaction predicted 34% of the variance in treatment adherence (β = 0.47, p < 0.001). Furthermore, patients with high levels of life satisfaction exhibited greater improvements in lung function (FEV1 +15.3%, p < 0.01) compared to those with low life satisfaction after 12 months of treatment. These findings extend the results of Johnson et al. (2019) and Zhang et al. (2021) by demonstrating the moderating effects of age (β = -0.22, p < 0.05) and disease duration (β = -0.18, p < 0.05) on this relationship. In contrast to the findings of Ramirez (2020), this study indicates that interventions aimed at enhancing life satisfaction (d = 0.76, 95% CI [0.62, 0.90]) significantly improve both treatment adherence and clinical outcomes for emphysema patients. Ultimately, the researchers emphasize the importance of integrating life satisfaction enhancement strategies into emphysema management, providing new insights into the complex interplay between psychosocial factors and treatment outcomes in this chronic condition.